Mathematics manual for water and wastewater treatment plant operators - Spellman, Frank R., author (Boca Raton : CRC Press, 2014)
"A comprehensive, self-contained mathematics reference, The mathematics manual for water and wastewater treatment plant operators will be useful to operators of all levels of expertise and experience. The text is divided into three parts. Part 1 covers basic math, Part 2 covers applied math concepts, and Part 3 presents a comprehensive workbook with more than 1700 sample problems highlighting the kinds of exam questions operators can expect to see on state licensure examinations. Readers working through the book systematically will acquire a definitive understanding of and skill in performing the applied water/wastewater calculations that are essential for a successful career"--provided by publisher